Growth and survival during drought: the link between hydraulic architecture and drought tolerance in grasses - Ocheltree, Troy W. (Kansas State University, 2012)
The pathway for the movement of water through plants, from the soil matrix to the atmosphere, constitutes the hydraulic architecture of a plant. The linkage between the hydraulic architecture of woody plants and drought tolerance has received considerable attention, but much less work has been done on grasses. I investigated the linkage between the hydraulic architecture of grasses to physiological patterns of water use across a range of species and conditions. The rate of stomatal conductance (g[subscript]s) and photosynthesis (A) increased acropetally along the leaves of 5 grass species, which is a unique feature of this growth form. The internal structure of leaves also changed acropetally in order to minimize the pressure gradient across the mesophyll that would otherwise occur as a result of increasing g[subscript]s. The resistance to water movement through the mesophyll represented 80-90% of leaf resistance in six genotypes of Sorghum bicolor L. (Moench). This resistance was most important in controlling g[subscript]s and A when water was readily available, but as soil-moisture decreased it was the efficient transport of water through the xylem that was most important in maintaining plant function. I also investigated the relationship between hydraulic architecture and stomatal responses of grasses to increasing Vapor Pressure Deficit (D). Grasses with a larger proportion of their hydraulic resistance within the xylem were less sensitive to increasing D and plants with high root conductance maintained higher rates of gas exchange D increased. Finally, I investigated the tolerance of grasses to extreme drought events to test if there was a trade-off between drought tolerance and growth in grasses. Plants with drought tolerant leaf traits typically sacrificed the ability to move water efficiently through their leaves. Having drought tolerant leaves did not limit the plants ability to have high rates of gas exchange, and, in fact, the most drought tolerant plants had the high rates of g[subscript]s when expressed on a mass basis. Leaf-level drought tolerance did contribute to species’ occurrence, as the drought intolerant species I studied are not commonly found in low precipitation systems. The results presented here highlight the importance of studying the hydraulic architecture of plants to provide a better understanding of what controls plant function across a range of environmental conditions.
Keywords: Plant Hydraulic Architecture; Drought Tolerance; Grass Anatomy; Grass Physiology; Stomatal Conductance; Agronomy (0285); Ecology (0329); Plant Biology (0309)